Effects of initial teamwork capability and initial relational capability on the development of new technology‐based firms - Brinckmann, Jan; Hoegl, Martin (Strategic Entrepreneurship Journal, 2011)
Abstract New technology‐based firms face substantial resource constraints. This study examines how teamwork capability and relational capability of the entrepreneurial team affects the development of new firms. Teamwork capabilities are captured by the quality of collaboration of the entrepreneurial team members among themselves. Relational capabilities are analyzed based on the collaboration of the entrepreneurial team members with partners external to the focal firm. Our findings show that teamwork and relational capabilities, while theoretically originating from social capabilities, can have diverging effects on the development of a new organization. We find that relational capabilities lead to founding team member additions as well as sales and employment growth. In contrast, teamwork capabilities lead to a reduced likelihood to add founding team members and do not affect sales and employment growth. Theoretical and practical implications are discussed. Copyright © 2011 Strategic Management Society.